2012
DOI: 10.1111/j.1468-0009.2011.00658.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Nurse Staffing Mandates on Safety‐Net Hospitals: Lessons from California

Abstract: Context: California is the first and only state to implement a patient‐to‐nurse ratio mandate for hospitals. Increasing nurse staffing is an important organizational intervention for improving patient outcomes. Evidence suggests that staffing improved in California hospitals after the mandate was enacted, but the outcome for hospitals bearing a disproportionate share of uncompensated care—safety‐net hospitals—remains unclear. One concern was that California's mandate would burden safety‐net hospitals without i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
49
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 53 publications
0
49
0
Order By: Relevance
“…For instance, California in the US implemented a mandate of a minimum patient-to-nurse staffing ratio, which has resulted in some success in improving nurse staffing in general as well as in hospitals serving vulnerable patients. 50 In addition, reshaping the current health care payment system may be considered in order to give hospitals more incentives to improve nurse work environment beyond strict regulations such as the readmission penalties. 27,34 In this review, it was found that readmissions were not uncommon and readmission rates were very high for some conditions.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, California in the US implemented a mandate of a minimum patient-to-nurse staffing ratio, which has resulted in some success in improving nurse staffing in general as well as in hospitals serving vulnerable patients. 50 In addition, reshaping the current health care payment system may be considered in order to give hospitals more incentives to improve nurse work environment beyond strict regulations such as the readmission penalties. 27,34 In this review, it was found that readmissions were not uncommon and readmission rates were very high for some conditions.…”
Section: Discussionmentioning
confidence: 99%
“…; McHugh et al. ). Finally, negative perceptions about the impact of SRNs on quality of care seem contrary to the large literature documenting an association between better nurse staffing and lower mortality (Kane et al.…”
mentioning
confidence: 99%
“…SRNs have been successfully used to reduce overtime and to provide coverage for weekends, holidays, and vacations, reportedly providing the same quality of care as permanent staff according to nurse managers (Warren and Rozell 1995). In California, the first state with mandated nurse staffing legislation, increased use of SRNs was associated with hospitals meeting mandated ratios, resulting in improved nurse staffing, including in safety net hospitals and possibly improved patient outcomes (Aiken et al 2010;McHugh et al 2012). Finally, negative perceptions about the impact of SRNs on quality of care seem contrary to the large literature documenting an association between better nurse staffing and lower mortality (Kane et al 2007;Aiken et al 2011;Needleman et al 2011), as presumably staffing with SRNs is an improvement over what staffing levels might have been in their absence.…”
mentioning
confidence: 99%
“…, McHugh et al . ). But it is well known that temporary nurses are paid higher wages than permanent staff, which can increase costs (May et al .…”
Section: Introductionmentioning
confidence: 97%